GAMBARAN KELUHAN MUSKULOSKELETAL DAN KELELAHAN SEBELUM DAN SETELAH BEKERJA PADA PEKERJA DI UD. BATU BUKIT - Utomo Wicaksono (JURNAL KEPERAWATAN SUAKA INSAN (JKSI), 2021)
Workers at UD. Batu Bukit in carrying out its work activities is exposed to working conditions that are not ergonomic. This is inseparable from the factors that carry the risk of danger that can cause problems in the form of musculoskeletal disorders and fatigue. The purpose of this study was to determine the musculoskeletal disorders and fatigue felt by workers before and after work. This study used an evaluative research design with a sample of 11 people. Data obtained by interview and using the Nordic Body Map questionnaire to measure musculoskeletal complaints before and after work and the 30 Items of Rating Scale questionnaire to measure fatigue before and after work. Data before and after working from these variables will be statistically analyzed with SPSS version 26.0. From the analysis, there was a significant increase in musculoskeletal disorders before and after work (p = 0.00; CI = 35.94-41.70) of 122.66% and there was a significant increase in fatigue before and after work (p = 0.00 ; CI = 45.34-49.39) of 132.22%. Working conditions at UD. Batu Bukit requires corrective actions to improve occupational health by considering the capabilities of small industries. Keywords: fatigue, musculoskeletal disorders, occupational health, small industries